MODEL KOREKSI KESALAHAN ANTARA BETA SAHAM, SUKU BUNGA DAN RETURN SAHAM DI INDONESIA - Yudhistira Ardana (Jurnal Bisnis Darmajaya, 2019)
This study aims to determine the effect of long-term and short-term beta between shares and BI interest rates on Stock Returns. The variables in this study are stock returns, beta stocks and BI interest rates. The sample used in this study is 40 companies registered in the LQ-45 index in the 2015-2016 period. The model used in this study is by using an error correction model (ECM). The results of the study show that beta stocks have a significant influence on stock returns in the long and short term. While the BI interest rate has a long-term significant effect on stock returns and in the short term does not affect stock returns. Simultaneously, stock beta and BI interest rates have a significant influence on stock returns.Keywords — beta stocks, BI interest rates, stock returns.